2021
DOI: 10.1038/s41598-020-79786-x
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering multi-faceted taxonomic and functional diversity of soil bacteriomes in tropical Southeast Asian countries

Abstract: Environmental microbiomes encompass massive biodiversity and genetic information with a wide-ranging potential for industrial and agricultural applications. Knowledge of the relationship between microbiomes and environmental factors is crucial for translating that information into practical uses. In this study, the integrated data of Southeast Asian soil bacteriomes were used as models to assess the variation in taxonomic and functional diversity of bacterial communities. Our results demonstrated that there we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 85 publications
1
0
0
Order By: Relevance
“…Moreover, compared to nirK-encoding denitrifiers, the variety of nirS-encoding denitrifiers was also greater, which is consistent with previous studies (Shi et al, 2019b;Ming et al, 2021). In general, nirS-and nirK-encoding denitrifiers had different respond to environmental parameters, and nirS denitrifiers had better adaptation to the coastal environments (Jones and Hallin, 2010;Likhitrattanapisal et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, compared to nirK-encoding denitrifiers, the variety of nirS-encoding denitrifiers was also greater, which is consistent with previous studies (Shi et al, 2019b;Ming et al, 2021). In general, nirS-and nirK-encoding denitrifiers had different respond to environmental parameters, and nirS denitrifiers had better adaptation to the coastal environments (Jones and Hallin, 2010;Likhitrattanapisal et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…This highlights the critical influence of climate on community structure, aligning with previous findings where specific taxa formed links within distinct environments 6 , 18 . Prior studies have also identified variations in both taxonomic and functional diversity across different geographic locations, influenced by soil characteristics such as soil class and pH levels 18 , 30 . Even more climate-specific patterns are observed at lower taxonomic levels, the majority of which comprise unassigned species.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the specific functions and contributions of these communities in their respective environments will provide a more comprehensive understanding of their ecological significance and potential implications for various ecosystems. It is also important to investigate how additional factors influence the biodiversity of a given area, as noted by previous works 30 , 36 , 37 . Finally, the present study mainly focused on bacterial communities at the EMPO3 “Soil (non-saline)” level.…”
Section: Discussionmentioning
confidence: 99%